Experimental and numerical research on rotating detonation combustor under non-premixed conditions. (20th March 2020) - Jin, Shan; Qi, Lei; Zhao, Ningbo; Zheng, Hongtao; Meng, Qingyang; Yang, Jialong
Abstract: In order to investigate the formation process and propagation characteristics of detonation wave, developing process of detonation wave from initiation to stable detonation formation under non-premixed conditions has been studied by experiments and numerical simulation. The results show that when mass flow rates of air and hydrogen are 158.957 g/s and 2.728 g/s respectively, stable detonation can be formed in the combustor. Due to the lower inlet pressure, there is an unstable stage in combustor before the stable detonation is formed. Reducing the air pressure will increase the lowest detonation limit of combustor and lead to flame-out and re-initiation in the combustor. The propagation direction of detonation wave may change after re-initiation. Non-premixed intake structure lead to the inconsistency of rotating detonation combustion fluid in the radial direction. Moreover, peak pressure appears near the outer wall, while peak temperature appears near the inner wall. Highlights: Hydrogen-air rotating detonations under low total air pressure were obtained. Low total air pressure disturbs rotating detonation. Re-initiations of RDWs were discovered. The propagation direction of RDW changes randomly after re-initiations. Differences of temperature and pressure on the inner and outer wall were discovered.